Description of the adult stage of Cercobrachys peruanicus (Ephemeroptera: Caenidae) - Molineri, Carlos (2006)
Adults of both sexes of Cercobrachys peruanicus Soldán are described for the first time and the genus and species are reported from Bolivia. Diagnoses, illustrations, and environmental data are provided. Adults of C. peruanicus can be distinguished from the other species of the genus by the following combination of characters: many (8–16) cross veins in the fore wings, penes lobes completely fused, with posterior margin straight, and styliger plate with a broad median emargination posteriorly.Cercobrachys peruanicus Soldán are described for the first time and the genus and species are reported from Bolivia. Diagnoses, illustrations, and environmental data are provided. Adults of C. peruanicus can be distinguished from the other species of the genus by the following combination of characters: many (8–16) cross veins in the fore wings, penes lobes completely fused, with posterior margin straight, and styliger plate with a broad median emargination posteriorly.C. peruanicus can be distinguished from the other species of the genus by the following combination of characters: many (8–16) cross veins in the fore wings, penes lobes completely fused, with posterior margin straight, and styliger plate with a broad median emargination posteriorly.can be distinguished from the other species of the genus by the following combination of characters: many (8–16) cross veins in the fore wings, penes lobes completely fused, with posterior margin straight, and styliger plate with a broad median emargination posteriorly.